A new genus of Cedriini (Hymenoptera: Braconidae, Hormiinae) from the Brazilian cerrado - Gibertoni, Julia; Whitfield, James B.; Penteado-Dias, Angélica M. (Zootaxa, 2021)
A new genus of the braconid wasp tribe Cedriini, Sagarana n. gen., (Hymenoptera, Braconidae) is described and illustrated from the Brazilian cerrado based on a newly discovered species, Sagarana cerradensis n. sp. The genus is clearly distinct from the other genera of the Cedriini, with unusual fringed depressions on the second metasomal sternite that are of unknown function. The confusing taxonomy of this tribe is briefly discussed.